Pengaruh Independensi Auditor, Good Corporate Governance Dan Kualitas Audit Terhadap Integritas Laporan Keuangan - Mahesa Deni Dwi Permana; Suzy Noviyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The object of this research is manufacturing companies in Indonesia which are listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The purpose of this study is to obtain knowledge about the influence of auditor independence, good corporate governance by examining the number of independent commissioners and audit committees, and quality audit of the integrity of financial statements. The data used are the annual financial statements of each manufacturing company listed on the Indonesia Stock Exchange from 2017 to 2019. This study used 31 manufacturing companies selected using purposive sampling technique with a population of 167 companies. This research is a quantitative study with the program used in data processing is Statistical Product and Service Solution (SPSS). The analysis of this study used multiple regression analysis and the significance value of each variable was measured using the t-test. The results of this study indicate that auditor independence has a significant effect on the integrity of financial statements, while independent commissioners, audit committee and audit quality have no significant effect on the integrity of financial statements. Keywords: Auditor Independence, Good